Phonological Interference in Pronouncing English Sounds among Lombok’s Senior High School Students - Eka Alfansyah; Hery Rahmat; Ribahan Ribahan (ELITE Association Indonesia, 2023)
The objectives of this research are to find out the phonological interference occurs and factors that cause interference in pronouncing English sound on vowel and consonant sounds by students on Senior High School in Lombok. This research used descriptive-qualitative method and applied purposive sampling techniques with inclusion criteria. The respondents consisted 10 second grade Senior High School students. The data were collected by using audio recorder and interview. The finding of this research showed the interference that occurs on students of second grade is substitution, sound addition, sound omission and sound replacement. There were 36 type of interference occurred, namely sounds replacement or substitution made by students in pronouncing English sounds consisting 31 vowels, 3 consonants, 3 sound addition and 2 sound omission. Further, the factor affect phonological interference of students was linguistic factors. It was found that majority students who answered that the difficulty in pronouncing English sounds were in pronunciation itself, while another factor were deal with sound system differences between L1 and L2, inconsistency of English vowels, mother tongue interference and influence of spelling on pronunciation.